Simultaneous en-bloc robot-assisted radical cystectomy and nephro-ureterectomy: technique description, outcomes, and literature summary. Issue 4 (December 2016) - Buse, Stephan; Hach, Carolin; Alexandrov, Assen; Mager, Rene; Haferkamp, Axel
Abstract The objectives of this study are to describe the surgical technique for simultaneous en-bloc robot-assisted radical cystectomy and nephro-ureterectomy, to report its surgical bench marks, and finally, to summarize the current evidence on the procedure. After written informed consent, we prospectively enrolled consecutive patients undergoing simultaneous en-bloc robot-assisted radical cystectomy and nephro-ureterectomy in a prospective institutional database. We performed all procedures with robotic assistance from the DaVinci Si-HD®, a four-arm robotic system. Endpoints included surgery duration, estimated intra-operative blood loss, resection margins, intra-, and post-operative complications. Furthermore, we describe oncological outcome at follow-up. We conducted six (54.4 %) right-sided and five (45.5 %) left-sided nephro-ureterectomies. Urinary diversion consisted in nine (81.2 %) ureterocutaneostomies and in two (18.8 %) ileum conduits. The median surgery duration was 287 min [interquartile range (Q1–Q3) 253–328], thereof 196-min console time (Q1–Q3 158–230). The median-estimated blood loss was 235 mL (Q1–Q3 200–262). We did not register any intra-operative complications or conversions to open surgery. Post-operatively, each one patient suffered a Clavien-Dindo grade 1 (paralytic ileus), grade 2 (blood transfusion), and grade 3 complication (port hernia). After a median follow-up of 7 months (Q1–Q3 4–25), we registered one recurrence, a metachronous transitional cell cancer of the contralateral kidney 24 months after the initial procedure. En-bloc robot-assisted radical cystectomy and nephro-ureterectomy was associated with limited procedure duration, minor blood loss and satisfying intra- and post-operative outcomes.